Production of β-lactamase inhibitors by Streptomyces species - Viana Marques, Daniela de Araújo; Machado, Suellen Emilliany Feitosa; Carvalho Santos Ebinuma, Valéria [UNESP]; Duarte, Carolina de Albuquerque Lima; Converti, Attilio; Porto, Ana Lúcia Figueiredo (MDPI, 2018)
β-Lactamase inhibitors have emerged as an effective alternative to reduce the effects of resistance against β-lactam antibiotics. The Streptomyces genus is known for being an exceptional natural source of antimicrobials and β-lactamase inhibitors such as clavulanic acid, which is largely applied in clinical practice. To protect against the increasing prevalence of multidrug-resistant bacterial strains, new antibiotics and β-lactamase inhibitors need to be discovered and developed. This review will cover an update about the main β-lactamase inhibitors producers belonging to the Streptomyces genus; advanced methods, such as genetic and metabolic engineering, to enhance inhibitor production compared with wild-type strains; and fermentation and purification processes. Moreover, clinical practice and commercial issues are discussed. The commitment of companies and governments to develop innovative strategies and methods to improve the access to new, efficient, and potentially cost-effective microbial products to combat the antimicrobial resistance is also highlighted.
Keywords: Actinobacteria; Antibiotic; Resistance; β-lactamase; β-lactamase inhibitor